2022
DOI: 10.3390/ijms23126725
|View full text |Cite
|
Sign up to set email alerts
|

Helena’s Many Daughters: More Mitogenome Diversity behind the Most Common West Eurasian mtDNA Control Region Haplotype in an Extended Italian Population Sample

Abstract: The high number of matching haplotypes of the most common mitochondrial (mt)DNA lineages are considered to be the greatest limitation for forensic applications. This study investigates the potential to solve this constraint by massively parallel sequencing a large number of mitogenomes that share the most common West Eurasian mtDNA control region (CR) haplotype motif (263G 315.1C 16519C). We augmented a pilot study on 29 to a total of 216 Italian mitogenomes that represents the largest set of the most common C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…These Swedish mtDNA datasets showed lower HVS/CR haplotype diversity compared to those from other populations in Europe. With the analysis of the entire mitogenome, the number of unique haplotypes could increase dramatically, potentially to a 100% resolution of common HVS/CR haplotypes, as observed in other West Eurasian populations [7][8][9]18]. Studies have, moreover, concluded that there is no significant substructure within Sweden based on mtDNA HVS/CR and Y-chromosomal markers [16,17,19,20], which has also been confirmed with autosomal DNA studies [21,22].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…These Swedish mtDNA datasets showed lower HVS/CR haplotype diversity compared to those from other populations in Europe. With the analysis of the entire mitogenome, the number of unique haplotypes could increase dramatically, potentially to a 100% resolution of common HVS/CR haplotypes, as observed in other West Eurasian populations [7][8][9]18]. Studies have, moreover, concluded that there is no significant substructure within Sweden based on mtDNA HVS/CR and Y-chromosomal markers [16,17,19,20], which has also been confirmed with autosomal DNA studies [21,22].…”
Section: Introductionmentioning
confidence: 70%
“…The comparisons, which ignored all indels, were performed using two approaches for matching: literal (e.g., a Y only matches a Y at a position) and pattern (e.g., a Y matches a C or T at a position). Additionally, summary statistics were calculated based on the two HVS regions (HVS1 nps 16,024-16,365 and HVS2 nps 73-340), CR (16,024-16,569, 1-576), and the entire mitogenome (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)569).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGS sequencing of the mtGenome has permitted improved resolution of the most common West Eurasian mtDNA control region haplotype [ 497 ]. Phylogenetic alignment and haplogroup classification have continued to be refined with new sequence information [ 498 ], and new assays have been developed to aid haplogroup classification [ 499 ].…”
Section: Emerging Technologies Research Studies and Other Topicsmentioning
confidence: 99%
“…Nowadays, the extensive mtDNA typing of population data and the establishment of dedicated databases such as EMPOP (www.empop.org) provide as many as possible mitogenomes at a maximum level of resolution and quality. Phylogeographic investigations conducted on local populations distributed worldwide ( [61][62][63][64] as examples) constantly contribute toward the definition of reference population databases to be used at a microgeographic level. A branch of forensic genetics that frequently uses mitochondrial polymorphisms in conjunction with DNA barcoding is wildlife forensics, which deals with crimes perpetrated against protected species.…”
Section: Genetic Markers Used In the Forensic Fieldmentioning
confidence: 99%